In Silico Engineering of Disulphide Bonds to Produce Stable Cellulase - Barati, Bahram; Sadegh Amiri, Iraj.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This Brief highlights different approaches used to create stable cellulase and its use in different fields. Cellulase is an industrial enzyme with a broad range of significant applications in biofuel production and cellulosic waste management. Cellulase 7a from Trichoderma reesei is the most efficient enzyme in the biohydrolysis of cellulose. In order to improve its thermal stability, it can be engineered using a variety of approaches, such as hydrophobic interactions, aromatic interactions, hydrogen bonds, ion pairs and disulfide bridge creation.
Introduction of Cellulose and its Application -- Literature Review -- Methodology of Mutant Creation and Molecular Dynamic Simulation -- Results and Discussions -- Conclusions.
Keywords: Energy; Renewable energy resources; Biochemical engineering; Chemoinformatics; Chemical engineering; Bioinformatics; Computational biology; Renewable energy sources; Alternate energy sources; Green energy industries; Energy; Renewable and Green Energy; Computer Applications in Chemistry; Industrial Chemistry/Chemical Engineering; Computer Appl. in Life Sciences; Biochemical Engineering; Electronic books